Potential Microbial Contamination on Kebab Meat in the Area of University of Muhammadiyah Malang - Bayu Etti Tri Adiyastiti; Rio Lingga; Syaiful Arifin; Listiari Hendraningsih (Faculty of Animal Science Universitas Brawijaya, 2019)
The aim of this research was to find the safety level of consuming kebab meat in the University of Muhammadiyah Malang campus area in terms of the number of microbial total plate count, Salmonella, E. coli, and S. aureus. The research was conducted with 2 treatments and 2 replications. The first observation was done during the outlet opening time and the second observation was around 8 hours after or when the outlet was going to be closed. Each treatment was sampled at 4 kebab outlets with different brands in the UMM area, so the total was 16 samples for laboratory analysis. The sample is directly pack in sterile bag, labeled sample code and bring them to the laboratory. The sample was taken to microbiology analysis in laboratory. The result showed the number of bacteria of 2 outlets with contamination levels exceeding the maximum limit set by Indonesia National Standards (SNI). The highest total bacteria count is owned by 4th outlet which is 2, 2×105± 0, 85×105 CFU/gram (daytime) and 4 4, 3×105± 2, 97×105 CFU/gram (night). The lowest Total bacteria is owned by 1st outlet, neither daytime nor evening bacterial colonies are found. Identification Salmonella, E. coli, and Staphylococcus aureus for all outlets are negative. The conclusion of this study is that two of the four kebab outlets in the UMM area was detected the bacteria total counts above of the contamination limit set by SNI 7388: 2009 and all of kebab’s meat were negative identified or did not contain Escherichia coli, Staphylococcus aureus, and Salmonella.